Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Bistable dynamic coordination polymer showing reversible structural and functional transformations - Nagarkar, Sanjog S.; Das, Raja; Poddar, Pankaj; Ghosh, Sujit K. (Inorganic Chemistry, 2012)
A bistable dynamic coordination polymer [Ni(pca)(bdc)(0.5)(H2O)(2)] having a two-dimensional (2D) zigzag sheet structure is synthesized solvothermally. Topological analysis revealed that the frameworks have an hcb type of uninodal net. The compound exhibits guest specific reversible structural transformations accompanying reversible changes in physical properties driven by inherent flexibility and transformability.

Biomilling of rod-shaped ZnO nanoparticles: a potential role of saccharomyces cerevisiae extracellular proteins - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
There is a tremendous interest in newly-discovered, green, room-temperature, biological routes for the fabrication of biologically-benign functional nanostructures. The bottom-up biogenic synthesis, where the precursor molecules form crystalline solids at the nanoscale by a redox process, has been validated over the years and gained its popularity. However, a new top-down technique has recently been developed by our group, in which small isotropic nanoparticles (NPs) are formed by the break-down of chemically-synthesized anisotropic rod or plate-shaped NPs using microbes (termed as biomilling). This technique, which holds great promise, is still in its infancy. Here, an improved process with an easy isolation of NPs from the biomass and better control of the technique is reported. This novel technique is demonstrated to break-down the chemically synthesized ZnO nanorods (NRs), similar to 250 nm in length, to small quasi-spherical ZnO NPs (similar to 10 nm in diameter) possibly due to the proteins secreted by the yeast (Saccharomyces cerevisiae), which also led to the formation of `` corona'' around the NPs. The UV-vis, PL and FTIR results show the dynamic nature of the protein corona, which is further supported by the SDS-PAGE study of the extracellular proteins. The SDS-PAGE study of the intracellular proteins shows the over-expression of a single protein which is supposed to have a role in zinc transport in the cells. The ICP-OES results show the accumulation of a higher amount of zinc in the yeast cells as biomilling progresses, while the extracellular zinc contents were almost same. Therefore, we believe that the yeast cells play an important role in the biomilling process by secreting the proteins and maintaining the zinc content in the extracellular fluid. The biomilled NPs exhibit a uniform dispersity and better aqueous stability than chemically synthesized ZnO NRs.

Broad spectrum photon responsive, paramagnetic beta-NaGdF4: Yb3+, Er3+ - mesoporous anatase titania nanocomposite - Padhye, Preeti; Sadhu, Subha; Malik, Monika; Poddar, Pankaj (RSC Advances, 2016)
Herein, we report a novel single multifunctional platform based on broad-spectrum photoactive beta-NaGdF4:18% Yb3+, 2% Er3+ and mesoporous anatase TiO2 for enhanced energy and simultaneous biomedical applications. Currently, the photoactive materials for solar energy harvesting applications have limitations in their efficiency due to their narrow photon absorption spectrum. The upconversion phosphor beta-NaGdF4: 18% Yb3+, 2% Er3+ nanorods collect and harvest the NIR photons (similar to 980 nm) of sunlight and transform them into visible light via anti-Stokes emission (lambda(em) similar to 521 and similar to 540 nm), and the photoactive mesoporous anatase TiO2 (mTiO(2)) utilizes UV and weak visible photons, thus the composite forms a broad spectrum photon-capture system and improved power conversion efficiency for enhanced applications in photocatalysis, and dye sensitized solar cells (DSSCs). The photocatalytic activity of the nanocomposite showed an improvement in comparison to the mTiO(2) for the degradation of various dyes. In addition, the photocurrent density and solar cell efficiency of the nanocomposites showed an improvement by similar to 24% and similar to 17% respectively, over mTiO(2). The beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite exhibits a strong paramagnetic signal (chi similar to 6.45 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed large longitudinal T1 relaxivity (r(1) = 7.09 s(-1) mM(-1)) and magnetic resonance imaging showed enhanced T-1-weighted MRI images with increased concentrations of beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite making them suitable for simultaneous magnetoresonance imaging. In addition, this composite system can also be used as a NIR triggered drug delivery system and in biomedical applications. Moreover, mesoporous TiO2 is expected to increase the photocatalytic active sites, dye, and absorption, and drug loading capacity. The as-designed multifunctional beta-NaGdF4:Yb3+, Er3+/mTiO(2) nanocomposite possessed simultaneous multiple discrete functionalities with excellent luminescence properties, intrinsic paramagnetism, biocompatibility, improved photocatalytic activity, and solar cell efficiency. This work provides a promising system to utilize NIR light, which will contribute to efficient photon harvesting and biological applications.